2000
DOI: 10.1017/s1360674300000265
|View full text |Cite
|
Sign up to set email alerts
|

Preposition stranding with wh-relatives: a historical survey

Abstract: In the course of their history, English wh-relatives are known to have undergone a syntactic change in their prepositional usage: having originally occurred only with piedpiped prepositions, they came to admit preposition stranding as an alternative pattern. The present article presents an overview of this process, showing a modest beginning of stranding in Late Middle English, an increase in Early Modern English, and then a clear decrease in the written language of today, against a more liberal use in spoken … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…In support of this prediction, previous studies have reported that stranding is acquired earlier and is more acceptable than fronting across various learner populations (Bardovi‐Harlig, ; Kao, ; McDaniel, McKee, & Bernstein, ; Rezai, ; Sadighi, Parhizgar, & Saadat, ; Sugisaki & Snyder, ). However, as Hoffmann and others have demonstrated, the distribution of fronting and stranding in language use depends on various contextual factors, for example, clause type, syntactic function of the prepositional phrase within the clause, level of formality, discourse context, type of embedding phrase, selection of the relativizer, finiteness, complexity and restrictiveness of the relative clause, and idiosyncratic effects of particular prepositions, prepositional verbs, and antecedent nouns (see also Bergh & Seppänen, ; Gries, ; Guy & Bayley, ; Hornstein & Weinberg, ; Johansson & Geisler, ; Takami, ; Trotta, ). As mentioned previously, interrogative (Example 1), oblique wh relative clauses (Example 2), preposing clauses, and exclamatives allow prepositions to be either fronted or stranded, whereas prepositions need to be stranded in non‐ wh relative clauses (Example 3) as well as in comparative, hollow, and passive clauses.…”
Section: Background Literaturementioning
confidence: 99%
“…In support of this prediction, previous studies have reported that stranding is acquired earlier and is more acceptable than fronting across various learner populations (Bardovi‐Harlig, ; Kao, ; McDaniel, McKee, & Bernstein, ; Rezai, ; Sadighi, Parhizgar, & Saadat, ; Sugisaki & Snyder, ). However, as Hoffmann and others have demonstrated, the distribution of fronting and stranding in language use depends on various contextual factors, for example, clause type, syntactic function of the prepositional phrase within the clause, level of formality, discourse context, type of embedding phrase, selection of the relativizer, finiteness, complexity and restrictiveness of the relative clause, and idiosyncratic effects of particular prepositions, prepositional verbs, and antecedent nouns (see also Bergh & Seppänen, ; Gries, ; Guy & Bayley, ; Hornstein & Weinberg, ; Johansson & Geisler, ; Takami, ; Trotta, ). As mentioned previously, interrogative (Example 1), oblique wh relative clauses (Example 2), preposing clauses, and exclamatives allow prepositions to be either fronted or stranded, whereas prepositions need to be stranded in non‐ wh relative clauses (Example 3) as well as in comparative, hollow, and passive clauses.…”
Section: Background Literaturementioning
confidence: 99%
“…At the same time that preposition stranding is gaining in frequency (Early Modern English), NP remnants remain less frequent than PP remnants, and at the time that the use of preposition stranding is suppressed due to the 18th-century normative pressures, NP remnants gain in frequency. There is evidence that the frequency of preposition stranding is high in the late 17th century, but suddenly drops in the late 18th century (Bergh & Seppänen, 2000; Yánez-Bouza, 2006). This sudden change is argued by Yánez-Bouza (2006) to be due to different attitudes to language: while the 17th century promotes conversational style, the 18th century comes with restrictions against what is perceived as incorrect usage.…”
Section: Datamentioning
confidence: 99%
“…Still, Hoffmann (2005, p. 263) reports that few prepositions in contexts admitting variability were stranded in ICE-GB; pied-piping accounted for 92% of the wh -relative clauses. Studies of other corpora of contemporary educated spoken British English (Johansson & Geisler, 1998; Quirk, 1957, cited in Bergh & Seppänen, 2000) likewise found stranding to be relatively rare (under 21%), albeit more frequent, if not the norm (Herrmann, 2003) in the “dialects”. Such inter-dialectal differences in stranding rates raise the question of the strength of the target model, a key, though understudied, predictor of convergent change.…”
Section: Introductionmentioning
confidence: 95%